EFFECT OF DIFFERENT BREEDING SYSTEMS OF AWASSI FLOCKS OF SOME REPRODUCTIVE TRAITS AND BODY MEASUREMENTS - Adhab, Ahmad Ali; Al -Jalili, Zuhair Fakhri; Taha, Sadeq Ali (Diyala Agricultural Sciences Journal, 2015)
This study was conducted at two locations, the 1st was at the breeding station of the sheep and goat which belongs to the States Board of Agricultural Researchers/ Ministry of Agriculture which located in Akarkouf 25 Km west of Baghdad). The 2nd one was in a farm of sheep owner (Private sector) in Abu-Ghraib, during the period from 15/5/2011 to 15/4/2012 to study the different production system and breeding systems on some reproductive and productive performance of Awassi sheep. Study includes three flocks of Awassi sheep each one consist of 40 Awassi ewes. (The 1st was the improved flock and the 2nd was the unimproved flock (both of them belongs to the sheep and goats station) while the 3rd belong to the sheep owner). Grazing flock had higher (P<0.05) fertilization percentage (80%) as compared to the unimproved flock. Also the grazing flock showed higher value (P<0.01) in twining percentage. As well as results of the study showed that the grazing flock had lower chest (39.2 cm), abdomen circumference (38.74 cm), body width at pelvis (11.28 cm) and the shoulder (11.3 cm) and the body length (34.10 cm) at birth. The unimproved flock had higher body height at shoulder at pelvis, chest and abdominal circumference.